Synthesis of gold-amine nanoparticles of various sizes using two different methods - Sun, Yijun (Kansas State University, 2012)
The motivation for the preparation of gold nanoparticles includes their potential utility in sensors, nanoelectronics, and the vast basic knowledge we can gain from these novel materials. Colloids of gold nanoparticles are also one of the most stable and easiest to manipulate. Synthesizing gold nanoparticles with narrow size distribution, uniform shape, and good crystalline nature represents a significant challenge. Thiols were found to be very efficient capping ligands for the digestive-ripening process in our research group, during which a colloidal suspension in a solvent is refluxed at the solvent boiling temperature in the presence of a capping ligand to convert a highly polydispersed colloid into a nearly monodispersed one. The current thesis research focuses on using amines instead of thiols as the capping ligands, which were also found to have similar efficiency for this purpose. The major part of the work is devoted to understanding the digestive ripening of gold-amine colloids system, and the effect of the nature of the amine ligands. A noteworthy achievement of the current work is the ability to synthesize stable gold colloids with different sizes by using different amine ligands. A diverse set of instrumental techniques is used for the characterization of the gold nanoparticles.
Keywords: Gold nanoparticles; Amine; SMAD; Inverse Micelle; Chemistry (0485)